The Role of Hedonic Motivation in Influencing TikTok Use and How It Relates to Generation Z Characteristics - Flourensia Sapty Rahayu; Putri Nastiti; Theovano Arthajanvian (Advances in Human-Computer Interaction)
Conclusion: The study sheds light on the significant roles of curiosity, joy, and immersion in influencing users’ intention to use TikTok while also highlighting the limited influence of control as a motivating factor. How joy and curiosity may contribute to the intention to use TikTok in Gen Z are discussed. A possible explanation of how these findings are related to Gen Z characteristics is also discussed. The findings are anticipated to give platform designers and marketers valuable insights to create more immersive and engaging user experiences, particularly for the Gen Z audience.